1998
DOI: 10.1073/pnas.95.20.11745
|View full text |Cite
|
Sign up to set email alerts
|

The common marmoset: A new world primate species with limitedMhcclass II variability

Abstract: The common marmoset (Callithrix jacchus) is a New World primate species that is highly susceptible to fatal infections caused by various strains of bacteria. We present here a first step in the molecular characterization of the common marmoset's Mhc class II genes by nucleotide sequence analysis of the polymorphic exon 2 segments. For this study, genetic material was obtained from animals bred in captivity as well as in the wild. The results demonstrate that the common marmoset has, like other primates, appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 45 publications
1
78
0
2
Order By: Relevance
“…Hence, one would predict that primate species possessing limited or no polymorphism of -DRB region configurations would encode highly variable Mhc-DRB genes that are frequently exchanged by recombination. This has been documented for common marmosets, a New World monkey from the neotropical rain forests (32). In addition, the chicken has been reported to possess a "minimal essential Mhc" with two class II genes (43).…”
Section: Interspecies Comparisonsmentioning
confidence: 88%
“…Hence, one would predict that primate species possessing limited or no polymorphism of -DRB region configurations would encode highly variable Mhc-DRB genes that are frequently exchanged by recombination. This has been documented for common marmosets, a New World monkey from the neotropical rain forests (32). In addition, the chicken has been reported to possess a "minimal essential Mhc" with two class II genes (43).…”
Section: Interspecies Comparisonsmentioning
confidence: 88%
“…The mean lesion volume was 2.85 AE 1.28 mm 3 and the total lesion load 5.91 AE 4.68 mm 3 . Lesion appearance on brain MRI did not always coincide with an immediate increase of the neurological score.…”
Section: Kinetics Of Lesion Developmentmentioning
confidence: 90%
“…Owing to the sharing of the MHC class II allele Caja-DRB Ã W 12 0 1 , 100% of monkeys are susceptible to the induction of experimental autoimmune encephalomyelitis (EAE), a widely accepted experimental model of the chronic inflammatory disease multiple sclerosis (MS) (3,4). The marmoset thus provides a useful preclinical model for basic research and for the efficacy testing of new therapies that fail to work in animal models more distinct from humans, such as rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular analysis of the Mhc class II genes of the common marmoset revealed functional Mhc-DR and -DQ regions, and an apparently inactivated Mhc-DP region (5). On basis of the number of alleles found, it was concluded that the Caja-DQA and -DQB loci are oligomorphic.…”
mentioning
confidence: 99%
“…Genomic DNA was isolated from stable growing B cell lines, and exon 2 of the Caja-DRB genes was amplified by PCR (5). Sequence analysis was performed on an ABI prism 310 Genetic analyzer (Perkin-Elmer Applied Biosystems, Foster City, CA) using the ABI Prism dRhodamine terminator cycle sequencing ready reaction kit (Perkin-Elmer).…”
Section: Typing Of Caja Mhc Class IImentioning
confidence: 99%